Subitization and attentional engagement by transient stimuli. - Alston, L; Humphreys, G (2004)
A series of experiments investigated the visual selection of moving and static items during enumeration. Small numbers of visual targets can be enumerated with little increase in reaction time and error with set size, a process referred to as 'subitization'. The number of items that can be subitized' is typically between one and four and known as the subitization range. This study looked for evidence of subitizing of subsets of items presented on a computer display. Fast and accurate enumeration was found for random configurations of moving targets even when presented among static distracters. This was not the case for static targets presented among moving or transient distracters. RTs to these targets were longer and showed a steady increase in RT with target number, even in the subitization range. However, when static targets and moving distracters were presented foveally, fast enumeration/subitization of the static targets was again possible. This was not due to reduced inter-item spacing, since linear effects of the number of targets still emerged when stimuli were presented peripherally but the size-spacing ratio was matched to the foveal presentations. There was indication that instead performance reflected perceived differences in movement speed for stimuli presented in parafoveal and more peripheral retinal regions. In support of this, subitization of static items improved as the movement speed of the distracters increased. The data suggest that the processes supporting subitization are highly sensitive to dynamic stimuli and depend on the ease of segmentation between static and moving arrays.